(untitled) (Journal of Universal Excellence, 2026)
Research question (RV): How the work-life balance is reflected to achieve a quality of life? Purpose: The article aims to present the benefits for the individual and the organisation of a good work-life balance. Method: A qualitative method of reviewing domestic and foreign professional literature was used for examination. Results: Achieving work-life balance is a constant process that can be achieved through the efforts of both the organisation and the employees. Organization: With the right balance in the life of the individual, the organization also benefits, namely employees are happier, more productive, more innovative and improve the relationship with management. Company: Both individuals and organisations have an impact on work-life balance. A positive balance leads to happier and satisfied people who are more productive in both the private and work environments. Originality: The research is useful for the purpose of the learning process in the subject Quality of Life 2nd year of master’s degree in quality management, at the Faculty of Organizational Studies in Novo Mesto. Limitations/further research: Research could be upgraded to other factors that also affect the work-life balance.